The Development of Piano Teaching for Piano Pedagogy Course - Zhang, Xiaolin; Daoruang, Krisada (Journal of Ecohumanism, 2025)
As an ancient and beautiful form of music, piano education plays an important role in college music education. Piano teaching is an important part of college music education and an essential direction of music education research. However, there are still many problems in piano teaching. This study takes piano teaching methods and music education major college students as research objects in this context. This research aims to study and analyze 3 piano pedagogy methods, develop a piano teaching model manual for a piano pedagogy course, and use and evaluate my teaching model manual for a piano pedagogy course. Multiple research tools were used in this study, such as the literature research method, questionnaire, and experimental study. The three piano teaching methods are studied through the collection of literature and data. Meanwhile, the study explored and innovated piano teaching. A questionnaire survey was conducted among 80 sophomore students. These research methods aim to evaluate the impact of innovative pedagogy on improving piano-related quality for students majoring in higher music education. The findings reveal that each of the three teaching methods has its advantages and disadvantages; a suitable piano teaching method should have both the cultivation of skills and the skillful application of the piano, and the new piano teaching method has an excellent application effect in college music education, which can help students improve their piano playing skills and musical expression ability.